Compatibility of the Number of Room Attendant at Imara Hotel Palembang - Trisna Rahmania; Dilla Pratiyudha; Arrahman (Journal Hotspot, 2021)
This study was aimed at knowing the occupancys of room at Imara Hotel Palembang and finding out the suitability of the room attendant quantity. This study is quantitative descriptive method with observation, interview, and questionnaire data collection techniques. Based on the results of research, the room occupancy rate at Hotel Imara Palembang for the period January to July was 41% with information on the number of rooms available (15,264 rooms), occupied rooms (6,272 rooms), empty rooms (5,613) and empty rooms (8,989 rooms). Based on the results of the formula, the suitability of the number of room attendants at Hotel Imara Palembang is not in accordance with the occupancy rate of rooms, because has two room attendants, while requires three room attendants to carry out the operational process of cleaning guest rooms efficiently.